Lawsonia inermis: Review of Its Anti-inflammatory Properties and Therapeutic Potential - Hidayat, Nafisa Nurfatia; Musfiroh, Ida (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
Lawsonia inermis often referred to as henna has been utilized for millennia in many parts of the world in traditional medicine including antibacterial, antifungal, antioxidant, anticancer and immunomodulatory effects and also to treat various inflammatory conditions. This review aims to comprehensively evaluate the anti-inflammatory effects of L. inermis and its potential therapeutic applications. Primary methods included literature searches in scientific databases like PubMed, Scopus, Springer that analyzed the bioactive compounds and their effects on inflammation. L. inermis contains active compounds like lawsone, alkaloids, flavonoids, and tannins, which have been shown to reduce inflammation in various experimental settings by inhibiting the production of pro-inflammatory such as cytokines and enzymes. Studies conducted in vivo and in vitro have shown that effectivity of Lawsonia inermis is effective in lowering edema, healing wounds, and both acute and chronic inflammation which involve regulatory mechanism and mediators of inflammation signalling pathways. Promising outcomes in the treatment of contact dermatitis, wound healing, reduce symptoms and pain management have also been seen in clinical studies. L. inermis shows promise as a natural anti-inflammatory agent. However, further research is needed to fully understand its mechanisms of action and optimize its therapeutic applications, including investigating its potential interactions with other medications and identifying the optimal dosage and administration routes.